Gestão educacional e interdisciplinaridade: a organização de um curso de empreendedorismo para a contemporaneidade - Silva, Jerley Pereira da (2018)
The researcher’s 16-year experience in Educational Management has led him to different questions to elaborate this doctoral thesis. The instrument used in the writing of the thesis is the narrative mode, in order to expose his personal and professional trajectory. The researcher mentions and highlights the rise of awareness, through the studies on interdisciplinarity, and presents those studies in an innovative way. By using Fazenda’s records in classes from 2015 to 2018, the researcher selects Fazenda’s answers to various questions, which are highlighted in the opening of each chapter and also thoroughly contemplated in one single chapter. With this methodology, the reader will be in touch with Fazenda’s interdisciplinarity throughout the entire reading of the thesis. The educational manager researcher’s narrative indicates his concern with the constant improvement of knowledge and skills in his position, both in terms of qualification and practice. He proposes, to educational managers of the 21st century, the possibility of rethinking their function, so that, by including the study of interdisciplinary assumptions in their qualification, they are able to innovate. Throughout this research process, he implements a discipline which contemplates interdisciplinary projects in different courses, and invites researchers who are especially involved with practices to be part of the academic staff. The result of this experience contributes to this research and motivates the researcher to organize and implement a course on Entrepreneurship focused on contemporary issues